Case report: Portal and systemic venous gas in a patient with perforated duodenal ulcer: CT findings - Fam, Maged Nassef Abdalla (J Radiol Case Rep, 2014)
Gas within the portal circulation has been known to be associated with a number of conditions most commonly mesenteric ischemia and necrosis. Systemic venous gas is described with few conditions and is mostly iatrogenic in nature. We describe a case of combined portal and systemic venous gas detected by computed tomography in a patient with perforated duodenal ulcer.